The performance of a Jatropha fruit shelling machine and the future improvement - Lim, Bo Yuan; Shamsudin, Rosnah; Baharudin, B. T. Hang Tuah; Yunus, Robiah (Horizon Research Publishing, 2014)
The removal of shell from Jatropha seed can improve oil yield and quality during the oil extraction process in biodiesel production. A Jatropha shelling machine was evaluated to analyse its efficiency to separate between the seed and the shell. The machine consists of a compression system with rollers as the fruit cracking unit, a vibratory sifter with mesh as the separation unit and two collectors. Based on the findings, the separation efficiency was reported at 91.25%. The study also showed that the sifter failed to separate shell component from seed completely due to the irregular size and shape of broken shell. Therefore, an idea to use the blower as separation unit is proposed to supersede the sifter design. The performance of blower system to recover shell-free seed will be investigated throughout the future research.